Inter‐ and intraobserver agreement for CT measurement of mandibular and medial retropharyngeal lymph nodes is excellent in dogs with histologically confirmed oral melanoma. Issue 1 (12th October 2021) - Cotter, Brad; Zwicker, Lesley A.; Waldner, Cheryl; Randall, Elissa; Gagnon, Jerome; Wiebe, Sheldon; Cohen, Eli B.; Hespel, Adrien‐Maxence; de Swarte, Marie; Mayer, Monique N.
Abstract: Mandibular and medial retropharyngeal lymph nodes are routinely evaluated with CT when staging dogs with oral melanomas. While size alone is considered inadequate for detecting nodal metastasis, it is critical in evaluating treatment response, as clinical decisions are based on changes in size. It is common for different radiologists to measure the size of pre‐ and posttreatment lymph nodes in the same patient. The objective of this retrospective, observer agreement study was to evaluate the inter‐ and intraobserver agreement in measuring canine mandibular and medial retropharyngeal lymph nodes by a diverse population of veterinary radiologists and trainees. Fourteen dogs with documented oral melanoma and head CT studies identified from records of a single institution were included in this study. North American veterinary radiologists and trainees were recruited to measure the mandibular and medial retropharyngeal lymph nodes; in triplicate. Prior to performing the study measurements, participants completed a training tool demonstrating the lymph node measurements. Overall, interobserver intraclass correlation coefficient (ICC) was 0.961 (95% confidence interval [CI]: 0.946, 0.972) and intraobserver ICC was 0.977 (95% CI: 0.968, 0.983), indicating excellent agreement (ICC > 0.9 considered excellent). Similar findings were noted following sub‐analysis for most variables (experience, size, laterality, axis of measurement). These results suggest that follow‐up measurement of the long and short axis of the mandibular lymph nodes and short axis of the medial retropharyngeal lymph nodes in the transverse plane, performed by different veterinary radiologists using the same method of measure, should have minimal impact on clinical decision making.